The Effect of UTAUT Factors and Trust on GoPay Use Behavior: The Mediating Influence of Behavioral Intention - Nurjanah, Putri; Erislan, Erislan (Research Horizon, 2026)
This study is motivated by the rapid growth of digital payment services in Indonesia, particularly the increasing adoption of e-wallets that has shifted consumer transaction behavior toward digital platforms. However, high download rates do not always translate into active usage, indicating the importance of understanding the factors influencing actual use behavior. This research aims to analyze the effects of performance expectancy, effort expectancy, social influence, and trust on behavioral intention and use behavior in the context of GoPay adoption. A quantitative survey approach was applied using purposive sampling, involving 130 non-merchant GoPay users in DKI Jakarta. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that performance expectancy, social influence, and trust have positive and significant effects on behavioral intention and use behavior, while effort expectancy has a positive but non-significant effect. Behavioral intention is identified as the strongest predictor and a key mediating variable influencing actual usage. These findings imply that strengthening perceived benefits, trust, and social-driven engagement is essential to encourage sustained e-wallet usage, beyond merely improving ease of use or increasing application downloads.